2009
DOI: 10.1161/hypertensionaha.108.125617
|View full text |Cite
|
Sign up to set email alerts
|

Continued Improvement in Hypertension Management in England

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
112
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(129 citation statements)
references
References 11 publications
11
112
1
5
Order By: Relevance
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 91%
“…20,23 The hypertension care showed an improvement during 2003-2006 also in the Health Survey for England in 2006, particularly in women. 26 In the National Health and Nutrition Examination Survey during 1988-2004, hypertension prevalence increased significantly in all US older adults aged 60 years or over, 19 by race/ethnicity in both non-Hispanic white and black people. 27 In older men hypertension awareness, treatment and control increased significantly and the rates reached those seen in women.…”
Section: Discussionmentioning
confidence: 99%
“…2 In the UK, despite some improvements in BP levels over recent years, nearly half those with hypertension do not have optimum control. 3,4 These results concur with international community-based studies showing BP goals are achieved in only 25-40% of patients on hypertensive drug treatment. 3,5 Self-monitoring of blood pressure (SMBP) by patients at home is one strategy whereby hypertensive patients can participate in managing their condition.…”
Section: Introductionsupporting
confidence: 67%
“…Hypertension is quite common in industrialized countries, [1][2][3] including Japan, 4 and is an important risk factor for cardiovascular disease (CVD), renal disease and eye disorders. [5][6][7] Large randomized controlled studies and a meta-analyses have established that antihypertensive medications reduce CVD morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%